Victimhood in American Narratives of the War in Vietnam, 1st edition - Musiał, Aleksandra (Routledge, 2020)
This book revisits the American canon of novels, memoirs, and films about the war in Vietnam, in order to reassess critically the centrality of the discourse of American victimization in the country’s imagination of the conflict, and to trace the strategies of representation that establish American soldiers and veterans as the most significant victims of the war. By investigating in detail the imagery of the Vietnamese landscape recreated by American authors and directors, the volume explores the proposition that Vietnam has been turned into an American myth, demonstrating that the process resulted in a dehistoricization and mystification of the conflict that obscured its historical and political realities. Against this background, representations of the war’s victims—Vietnamese civilians and American soldiers—are then considered in light of their ideological meanings and uses. Ultimately, the book seeks to demonstrate how, in a relation of power, the question of victimhood can become ideologized, transforming into both a discourse and a strategy of representation—and in doing so, to demythologize something of the "Vietnam" of American cultural narrative.